Local government and local democracy in Sri Lanka : institutional and social dimensions - Uyangoda,Jayadewa; Uyangoda, Jayadeva; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 2015)
Contributed articles.
Includes bibliographical references and index.
Keywords: Local government -- Sri Lanka -- History; Democracy -- Sri Lanka; Political science -- Sri Lanka